Bryochoerus liupanensis sp. nov. and Pseudechiniscus chengi. sp. nov. (Tardigrada: Heterotardigrada: Echiniscidae) from China - Xue, Jing; Li, Xiaochen; Wang, Lizhi; Xian, Panpan; Chen, Huiqing (Zootaxa, 2017)
Two new species from China, Bryochoerus liupanensis sp. nov. and Pseudechiniscus chengi sp. nov. (Tardigrada: Heterotardigrada: Echiniscidae), are reported. Bryochoerus liupanensis sp. nov. is characterized by median plates 1 and 2 divided into four parts while median plate 3 is divided into three parts, and by two lateral plates on each side of all median plates. The new species differs from Bryochoerus intermedius in having a different cuticular sculpture and different lateral plates. Pseudechiniscus chengi sp. nov. is characterized by: head plate faceted, cephalic papilla dome-shaped, pseudosegmental plate with a longitudinal median fold, all plates including the dorsal plates and plates on legs with ornamentation composed of dense round dots, differing in size, and lacking striae between the dots. Pseudechiniscus chengi sp. nov. is most similar to Pseudechiniscus santomensis but differs by: lacking striae between the round dots on dorsal plates, lacking the tiny projections on the caudal margin of pseudosegmental plate, and the divided pseudosegmental plate.